A case series on the technical use of three‐dimensional image guidance in subaxial anterior cervical surgery. Issue 1 (13th February 2014) - Pirris, Stephen M.; Nottmeier, Eric W.
Abstract Background Three dimensional (3D) image guidance has been used to improve the safety of complex spine surgeries, but its use has been limited in anterior cervical spine approaches. Methods Twenty‐two patients underwent complex anterior cervical spine surgeries in which 3D image guidance provided intraoperative assistance with the dissection, decompression and implant placement. One of two paired systems, the BrainLAB (BrainLAB, Westchester, Illinois) system, or Stealth (Medtronic Inc., Littleton, Massachusetts) system was used for 3D image guidance in this study. Results Image guidance was able to reliably locate pertinent anatomical structures in complex anterior cervical spine surgery involving re‐exploration, dissection around vertebral arteries or deformity correction. No complications occurred, and no patients required a revision anterior surgery. Conclusion This technical note describes the setup and technique for the use of cone beam computed tomography (cbCT)‐based, 3D image guidance in subaxial anterior cervical surgery. The authors have found this technique to be a useful adjunct in revision anterior cervical procedures, as well as anterior cervical procedures involving corpectomy or tumor removal. Copyright © 2014 John Wiley & Sons, Ltd.